Comprehensive phenotyping revealed transient startle response reduction and histopathological gadolinium localization to perineuronal nets after gadodiamide administration in rats - Habermeyer, Johanna; Boyken, Janina; Harrer, Julia; Canneva, Fabio; Ratz, Veronika; Moceri, Sandra; Admard, Jakob; Casadei, Nicolas; Jost, Gregor; Bäuerle, Tobias; Frenzel, Thomas; Schmitz, Christoph; et al. (Scientific Reports, 2020)
Gadolinium based contrast agents (GBCAs) are widely used in clinical MRI since the mid-1980s. Recently, concerns have been raised that trace amounts of Gadolinium (Gd), detected in brains even long time after GBCA application, may cause yet unrecognized clinical consequences. We therefore assessed the behavioral phenotype, neuro-histopathology, and Gd localization after repeated administration of linear (gadodiamide) or macrocyclic (gadobutrol) GBCA in rats. While most behavioral tests revealed no difference between treatment groups, we observed a transient and reversible decrease of the startle reflex after gadodiamide application. Residual Gd in the lateral cerebellar nucleus was neither associated with a general gene expression pathway deregulation nor with neuronal cell loss, but in gadodiamide-treated rats Gd was associated with the perineuronal net protein aggrecan and segregated to high molecular weight fractions. Our behavioral finding together with Gd distribution and speciation support a substance class difference for Gd presence in the brain after GBCA application.
CRIS-Team WoS Importer:2021-01-22

Differential Levels and Phosphorylation of Type 1 Inositol 1,4,5-Trisphosphate Receptor in Four Different Murine Models of Huntington Disease - Post, Joakim Iver; Leergaard, Trygve B.; Ratz, Veronika; Walaas, S. Ivar; von Hörsten, Stephan; Nissen-Meyer, Lise Sofie H. (Journal of Huntington's Disease, 2019)
Background: The intracellular ion channel type 1 inositol 1,4,5-trisphosphate receptor (IP(3)R1) releases Ca-2(+) from the endoplasmic reticulum upon stimulation with IP3. Perturbation of IP(3)R1 has been implicated in the development of several neurodegenerative disorders, including Huntington disease (HD).
CRIS-Team WoS Importer:2019-09-13

EXPRESSION OF FKBP51 AND HAP40 PROTEIN IN A CONGENIC RAT MODEL OF HUNTINGTON DISEASE - Ratz, Veronika; Plank, Anne-Christine; Schulze-Krebs, Anja; von Hörsten, Stephan (2018)
EVALuna2:36093

Gene-dosage- and sex-dependent differences in the prodromal-Like phase of the F344tgHD rat model for Huntington disease - Ratz-Wirsching, Veronika; Habermeyer, Johanna; Moceri, Sandra; Harrer, Julia; Schmitz, Christoph; von Hörsten, Stephan (Frontiers in Neuroscience, 2024)
In Huntington disease (HD) the prodromal phase has been increasingly investigated and is currently in focus for early interventional treatments. Also, the influence of sex on disease progression and severity in patients is under discussion, as a sex-specific impact has been reported in transgenic rodent models for HD. To this end, we have been studying these aspects in Sprague Dawley rats transgenic for HD. Here, we took up on the congenic F344tgHD rat model, expressing a fragmented Htt construct with 51 CAG repeats on an inbred F344 rat background and characterized potential sexual dimorphism and gene-dosage effects in rats during the pre-symptomatic phase (1–8 months of age). Our study comprises a longitudinal phenotyping of motor function, emotion and sensorimotor gating, as well as screening of metabolic parameters with classical and automated assays in combination with investigation of molecular HD hallmarks (striatal cell number and volume estimation, appearance of HTT aggregates). Differences between sexes became apparent during middle age, particularly in the motor and sensorimotor domains. Female individuals were generally more active, demonstrated different gait characteristics than males and less anxiolytic-like behavior. Alterations in both the time course and affected behavioral domains varied between male and female F344tgHD rats. First subtle behavioral anomalies were detected in transgenic F344tgHD rats prior to striatal MSN cell loss, revealing a prodromal-like phase in this model. Our findings demonstrate that the congenic F344tgHD rat model shows high face-validity, closely resembling the human disease’s temporal progression, while having a relatively low number of CAG repeats, a slowly progressing pathology with a prodromal-like phase and a comparatively subtle phenotype. By differentiating the sexes regarding HD-related changes and characterizing the prodromal-like phase in this model, these findings provide a foundation for future treatment studies.
CRIS-Team Scopus Importer:2024-03-01
Keywords: behavioral phenotyping; gene-dosage; Huntington disease; prodrome; sex differences; striatal atrophy

Impaired striatal glutathione–ascorbate metabolism induces transient dopamine increase and motor dysfunction - Malik, Mohd Yaseen; Guo, Fei; Asif-Malik, Aman; Eftychidis, Vasileios; Barkas, Nikolaos; Eliseeva, Elena; Timm, Kerstin N.; Wolska, Aleksandra; Bergin, David; Zonta, Barbara; Ratz-Wirsching, Veronika; von Hörsten, Stephan; et al. (Nature Metabolism, 2024)
Identifying initial triggering events in neurodegenerative disorders is critical to developing preventive therapies. In Huntington’s disease (HD), hyperdopaminergia—probably triggered by the dysfunction of the most affected neurons, indirect pathway spiny projection neurons (iSPNs)—is believed to induce hyperkinesia, an early stage HD symptom. However, how this change arises and contributes to HD pathogenesis is unclear. Here, we demonstrate that genetic disruption of iSPNs function by Ntrk2/Trkb deletion in mice results in increased striatal dopamine and midbrain dopaminergic neurons, preceding hyperkinetic dysfunction. Transcriptomic analysis of iSPNs at the pre-symptomatic stage showed de-regulation of metabolic pathways, including upregulation of Gsto2, encoding glutathione S-transferase omega-2 (GSTO2). Selectively reducing Gsto2 in iSPNs in vivo effectively prevented dopaminergic dysfunction and halted the onset and progression of hyperkinetic symptoms. This study uncovers a functional link between altered iSPN BDNF-TrkB signalling, glutathione–ascorbate metabolism and hyperdopaminergic state, underscoring the vital role of GSTO2 in maintaining dopamine balance.
CRIS-Team Scopus Importer:2024-12-06

Young human alpha synuclein transgenic (BAC-SNCA) mice display sex- and gene-dose-dependent phenotypic disturbances - Moceri, Sandra; Bäuerle, Natascha; Habermeyer, Johanna; Ratz-Wirsching, Veronika; Harrer, Julia; Distler, Jörg; Schulze-Krebs, Anja; Timotius, Ivanna K.; Bluhm, Alexandra; Hartlage-Rübsamen, Maike; Roßner, Steffen; Winkler, Jürgen; et al. (Behavioural Brain Research, 2024)
Parkinson's disease (PD) is a common neurodegenerative movement disorder, characterized by the loss of dopaminergic neurons in the substantia nigra pars compacta and the accumulation of aggregated alpha synuclein (aSyn). The disease often presents with early prodromal non-motor symptoms and later motor symptoms. Diagnosing PD based purely on motor symptoms is often too late for successful intervention, as a significant neuronal loss has already occurred. Furthermore, the lower prevalence of PD in females is not well understood, highlighting the need for a better understanding of the interaction between sex and aSyn, the crucial protein for PD pathogenesis. Here, we conducted a comprehensive phenotyping study in 1- to 5-month-old mice overexpressing human aSyn gene (SNCA) in a bacterial artificial chromosome (BAC-SNCA). We demonstrate a SNCA gene-dose-dependent increase of human aSyn and phosphorylated aSyn, as well as a decrease in tyrosine hydroxylase expression in BAC-SNCA mice, with more pronounced effects in male mice. Phosphorylated aSyn was already found in the dorsal motor nucleus of the vagus nerve of 2-month-old mice. This was time-wise associated with significant gait altrations in BAC-SNCA mice as early as 1 and 3 months of age using CatWalk gait analysis. Furthermore, anxiety-related behavioral tests revealed an increase in anxiety levels in male BAC-SNCA mice. Finally, 5-month-old male BAC-SNCA mice exhibited a SNCA gene-dose-dependent elevation in energy expenditure in automated home-cage monitoring. For the first time, these findings describe early-onset, sex- and gene-dose-dependent, aSyn-mediated disturbances in BAC-SNCA mice, providing a model for sex-differences, early-onset neuropathology, and prodromal symptoms of PD.
CRIS-Team Scopus Importer:2024-01-12
Keywords: Alpha synuclein; Behavioral phenotyping; Gait analysis; Parkinson's disease; Sex difference; SNCA gene-dose